Corona Virus Disease 19 On Islamic Theological Reflection - Muhammad Rizky HK (UIN Mataram, 2022)
The Covid 19 pandemic has changed the entire structure of human life. From economic problems, social relations, to the most intimate parts of human life; Faith. Aqida as a foundation of religious belief in Islam, shaken by various theoretical problems, to answer questions; How does Islam from a theological reflection facing this pandemic situation? Through this article, the author demands to present a theological reflection in the face of the COVID-19 pandemic. By recollecting the thoughts of Islamic classical theology, with various ideologies and schools of thought in Islam as secondary sources, with the humanist theology’s approach this article seeks to provide theological perspective and reflection, to nurture religious beliefs, and provide theological explanations for the pandemic situation related to the Muslim community.